Edward Fitzgerald—pioneer, coach driver, shepherd, and rabitter : a very brief reflection - Rangiwai, Byron (Te Kaharoa, 2021)
My extended whānau, Edward Fitzgerald’s descendants, know very little about him. We know he was of Irish descent, and his death certificate notes that he was born in Tauranga to Tom Fitzgerald and Elizabeth Blackburn. His death certificate states that he died of chronic myocardial degeneration at Waiōhau at the age of 82. This very brief paper gathers the very few known strands of his history and merely describes what is known of him. This paper is published here in memory of him and to inspire whānau to continue searching for more information.